From pro-natalist rhetoric to population policies in Turkey? An OLG general equilibrium analysis - Georges, Patrick; Seckin, Aylin (Elsevier, 2016)
We build an overlapping generation (OLG) general equilibrium model of Turkey with survival rates and endogenous labour supply to simulate the economic, fiscal, welfare, and intergenerational redistribution impacts of the medium and high fertility demographic scenarios projected by the United Nations. We assume that the high fertility variant is a realistic demographic proxy for pro-natalist policies in Turkey, Our results show that on a purely economic basis, a higher fertility scenario in Turkey appears open to criticisms as it cannot offset the social security pressures of ageing, and it also involves intergenerational welfare redistributions so that current young adults are unlikely to endorse natalist rhetoric and policies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Demographic Transition; Pro-Natalist Policies; Social Security Reforms; Overlapping-Generation General Equilibrium Modelling; Turkey's Economy; Demographic-Transition; Fertility; Growth; Rates